RETRACTED: A Deep Insight Into CAR-T Cell Therapy in Non-Hodgkin Lymphoma: Application, Opportunities, and Future Directions - Marofi, Faroogh; Rahman, Heshu Sulaiman; Achmad, Muhammad Harun; Sergeevna, Klunko Nataliya; Suksatan, Wanich; Abdelbasset, Walid Kamal; Mikhailova, Maria Vladimirovna; Shomali, Navid; Yazdanifar, Mahboubeh; Hassanzadeh, Ali; Ahmadi, Majid; Motavalli, Roza; et al. (Frontiers in Immunology, 2021)
Abstract Non-Hodgkin's lymphoma (NHL) is a cancer that starts in the lymphatic system. In NHL, the important part of the immune system, a type of white blood cells called lymphocytes become cancerous. NHL subtypes include marginal zone lymphoma, small lymphocytic lymphoma, follicular lymphoma (FL), and lymphoplasmacytic lymphoma. The disease can emerge in either aggressive or indolent form. 5-year survival duration after diagnosis is poor among patients with aggressive/relapsing form of NHL. Therefore, it is necessary to understand the molecular mechanisms of pathogenesis involved in NHL establishment and progression. In the next step, we can develop innovative therapies for NHL based on our knowledge in signaling pathways, surface antigens, and tumor milieu of NHL. In the recent few decades, several treatment solutions of NHL mainly based on targeted/directed therapies have been evaluated. These approaches include B-cell receptor (BCR) signaling inhibitors, immunomodulatory agents, monoclonal antibodies (mAbs), epigenetic modulators, Bcl-2 inhibitors, checkpoint inhibitors, and T-cell therapy. In recent years, methods based on T cell immunotherapy have been considered as a novel promising anti-cancer strategy in the treatment of various types of cancers, and particularly in blood cancers. These methods could significantly increase the capacity of the immune system to induce durable anti-cancer responses in patients with chemotherapy-resistant lymphoma. One of the promising therapy methods involved in the triumph of immunotherapy is the chimeric antigen receptor (CAR) T cells with dramatically improved killing activity against tumor cells. The CAR-T cell-based anti-cancer therapy targeting a pan–B-cell marker, CD19 is recently approved by the US Food and Drug Administration (FDA) for the treatment of chemotherapy-resistant B-cell NHL. In this review, we will discuss the structure, molecular mechanisms, results of clinical trials, and the toxicity of CAR-T cell-based therapies. Also, we will criticize the clinical aspects, the treatment considerations, and the challenges and possible drawbacks of the application of CAR-T cells in the treatment of NHL.